AQX‐1125, small molecule SHIP1 activator inhibits bleomycin‐induced pulmonary fibrosis. (11th August 2017) - Cross, Jennifer; Stenton, Grant R; Harwig, Curtis; Szabo, Csaba; Genovese, Tiziana; Di Paola, Rosanna; Esposito, Emanuale; Cuzzocrea, Salvatore; Mackenzie, Lloyd F
Abstract : Background and Purpose: The phosphatase SHIP1 negatively regulates the PI3K pathway, and its predominant expression within cells of the haematopoietic compartment makes SHIP1 activation a novel strategy to limit inflammatory signalling generated through PI3K. AQX‐1125 is the only clinical‐stage, orally administered, SHIP1 activator. Here, we demonstrate the prophylactic and therapeutic effects of AQX‐1125, in a mouse model of bleomycin‐induced lung fibrosis. Experimental Approach: For prophylactic evaluation, AQX‐1125 (3, 10 or 30 mg·kg −1 ·d −1, p.o.) or dexamethasone (1 mg·kg −1 ·d −1, i.p.) were given to CD‐1 mice starting 3 days before intratracheal administration of bleomycin (0.1 IU per mouse) and continued daily for 7 or 21 days. Therapeutic potentials of AQX‐1125 (3, 10 or 30 mg·kg −1 ·d −1, p.o.) or pirfenidone (90 mg·kg −1 ·d −1, p.o.) were assessed by initiating treatment 13 days after bleomycin instillation and continuing until day 28. Key Results: Given prophylactically, AQX‐1125 (10 and 30 mg·kg −1 ) reduced histopathological changes in lungs, 7 and 21 days following bleomycin‐induced injury. At the same doses, AQX‐1125 reduced the number of total leukocytes, neutrophil activity, TGF‐β immunoreactivity and soluble collagen in lungs. Administered therapeutically, AQX‐1125 (10 and 30 mg·kg −1 ) improved lung histopathology, cellular infiltration and reduced lung collagen content. At 30 mg·kg −1, the effects of AQX‐1125 were similar to those of pirfenidone (90 mg·kg −1 ) with corresponding improvements in disease severity. Conclusions and Implications: AQX‐1125 prevented bleomycin‐induced lung injury during the inflammatory and fibrotic phases. AQX‐1125, given therapeutically, modified disease progression and improved survival, as effectively as pirfenidone.